Pemberdayaan Mading Santri 3 Dimensi Berkolaborasi dengan Ikatan Penulis Muda (IPM) - Ospa Pea Yuanita Meishanti; Ramadania Fitri Rawinda; Shofwatul Muflihat (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
Santriwati Pondok Pesantren Assaidiyyah 1 Bahrul Ulum Tambakberas, Jombang Regency has a little problem in experiencing extracurricular development, more precisely in IPM extracurricular activities. There are several obstacles / obstacles in the progress of these extra-curricular activities. In accordance with the demands of the millennial era, it is demanded to be creative and innovative in developing, but there is still much that needs to be improved, one of which is the interest of students and also the skills of the teachers who teach the extracurricular activities. Efforts to support the extra / progress of these students can be in a way or method they like, by studying or thinking in an open space so that their minds can imagine anywhere they like, for learning is now more student centered orientation. The long-term plan of community service activities in the KKN-PPM scheme is through developing and enhancing the skills of students or the millennial generation of Islamic boarding schools in increasing an interest in writing and working talents through 3-dimensional wall magazine activities and young writers' ties. Through this activity it is hoped that all Millennial generation students are more skilled and professional in creating an interest in writing and working talent because we are the younger generations who will be the pride of a nation.